Comprehensive Analysis of the Prognostic and Immunological Role of PAFAH1B in Pan-Cancer - Yuan, Yixiao; Jiang, Xiulin; Tang, Lin; Wang, Juan; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Mounting evidence has demonstrated that PAFAH1B3 plays a critical role in the cancer initiation, metastasis and progression, but there is no study focus on the diagnostic values, prognostic and immunology role of PAFAH1B3 in various types of cancer. In this study, we found that PAFAH1B3 was elevated in human pan-cancer, and its high expression was correlated with pathologic stage and poor prognosis in pan-cancer, especially in NSCLC and LIHC. Furthermore, we uncover that PAFAH1B3 expression was positively associated with tumor mutational burden (TMB), microsatellite instability (MSI), immune cell infiltration, immune-modulatory related genes and diverse cancer drug sensitivity in human cancer. Finally, we showed that increased PAFAH1B3 expression was correlated with poor overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) of NSCLC and LIHC, PAFAH1B3 has a potential as an independent risk factor for OS, DSS, and PFI in LIHC, KEGG enrichment analysis confirm that PAFAH1B3 mainly involve in immune response regulation. More importantly, our results demonstrated that PAFAH1B3 was up-regulation in liver cancer cells lines, knock down of PAFAH1B3 significantly inhibits the cell proliferation, migration and invasion abilities in LIHC. In summary, our study elucidates the clinical significance and biology functions of PAFAH1B3 in LIHC and provides a potential biomarker for diagnosis and prognosis across various cancer types.